Class-E Power Amplifier with Novel Pre-Distortion Linearization Technique for 4G Mobile Wireless Communications - Eswaran, U.; Ramiah, H.; Kanesan, J. (Elektronika ir Elektrotechnika, 2014)
A new method to improve the battery life span of a 4G handset power amplifier (PA) is proposed. This technique is realized by employing a novel passive linearization topology on a class-E PA. Implemented in a 2 µm InGaP/GaAs Hetero-Junction Bipolar Transistor (HBT) technology, the PA delivers 49 % of power added efficiency (PAE) at output power of 28 dBm while complying with the Long Term Evolution (LTE) regulation at Band 1(1920 MHz–1980 MHz) with corresponding supply voltage headroom of 4 V. The performance enhancement is achieved at LTE channel bandwidth of 20 MHz. To the best of the author’s knowledge, this is the first class-E PA which meets adjacent channel leakage ratio (ACLR) specifications at 20 MHz LTE bandwidth. DOI: http://dx.doi.org/10.5755/j01.eee.20.4.3185